The Effect of Wing Margin Shape Generalisation on the Aerodynamic Performance of a Bat Inspired Wing - Suhaimi, Shafiq; Shuib, Solehuddin; Yusoff, Hamid; Halim Kadarman, A. (International Journal of Engineering and Technology, 2018)
Bio-inspiration is a method of design that uses findings and observation from the field of biology and applying them in mechanical applications. In this study, bio-inspiration was used to develop a flapping wing for a Micro Air Vehicle. This is done by producing a wing geometry by tracing the margin shape of the wing. The trace was then used to generate vertices of 99, 49, 13, and 7 vertices. The vertices were then used to create a CAD drawing to calculate the lift, drag, and aerodynamic efficiency for each generated wing. The wing was set at 20 degrees angle of attack with a flapping frequency of 3Hz. The wing was set to increase and will then correlated to increasing advance ratio of 0.19 to 5.19. The results shows that each wing behaves similarly generating the highest lift at low advance ratio, and the generated lift decreases as the advance ratio increases. At low advance ratios, 99, 49, and 13 vertices wings have similar generated lift while 7 vertices wing has the lowest lift generation. However, at high advance ratios, the 7 vertices wing has the highest generated lift followed by the 13 vertices wing, and then the 4 vertices wing. The 99 vertices wing has the lowest generated lift. Similar patterns is observed for drag where at lower advance ratios, 7 vertices wings generates the least drag followed by 13, 49, and 99 vertices wing. At higher advance ratios, 99 vertices wing generates the least drag followed by 49, 13, and 7 vertices wing. As for aerodynamic efficiency, 7 vertices wing has the highest lift to drag ratio followed by 13, 49, and 99 vertices wing. This is due to the wing geometryâ€™s ability to generate wing tip vortex at high advance ratio. The study has shown that the act of geometry simplification can be used to improve upon a bio-inspired design.Â